Design and Simulation Converter with Buck-boost Converter as The Voltage Stabilizer - Suryadi, Aris; Tulus Asmoro, Purwandito; Sofwan, Agus (International Journal of Electrical, Energy and Power System Engineering, 2020)
Buck-boost Converter is the device with the function to convert DC Voltage input to the setpoint DC Voltage output. Buck-boost converter can be used for regulating unstable voltage became a stable voltage by the user’s needs. Using a Buck-boost Converter in the research is about how to apply a Buck-boost Converter of the AC to AC Converter device, AC to AC Converter is the device to convert AC voltage to AC Voltage where the voltage can be modified. In the research, the input Voltage of AC to AC Converter is unstable, so that the output Voltage is unstable too in the range of 190 V to 250 V. To solve this problem, that the Buck-boost can be installed to AC to AC Converter, it is useful to keep output Voltage stable even though the input Voltage is unstable. The AC to AC Converter device in this research consist of Rectifier, Buck-boost Converter, and Inverter. The experiment result of this research show that unstable AC input Voltage, 190 V to 250 V from the source after passing a Rectifier, became an unstable DC input Voltage, then be regulated by Buck-boost Converter became a stable DC Voltage, and then after passing the Inverter, a stable DC Voltage is converted became a stable AC Voltage, corresponding with the set point. For further development, AC to AC Converter combined with Buck-boost Converter can be applied to maintain a standard of Voltage 220 V AC from the sources to keep it stable.